The Effect of Computer Laboratory Facilities and Learning Interest on Students’ Learning Outcomes - Sulasteri, Sri; Nur, Fitriani; Suharti, Suharti (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This research aims to know the effect of computer laboratory facilities and learning interest on student’s learning outcomes. Used ex-post facto quantitative research with exogenous, endogenous, and intervening variables. Population and sample of this research were mathematics education department students for the 2020/2021 academic year, totaling around 80 people. The instruments used were questionnaires and written test. Data analysis technique used is path analysis. Based on the research that has been done, it’s concluded that: (1) description of computer laboratory facilities, students’ learning interest and students’ mathematics learning outcomes in order are in the medium, high, and high categories, (2) there is a direct effect of computer laboratory facilities on mathematics education department student’s mathematics learning outcomes, (3) there is a direct effect of learning interest on students’ mathematics learning outcomes, (4) there is a direct effect of computer laboratory facilities on mathematics education department student’s mathematics learning interest, and (5) there is an indirect effect of computer laboratory facilities on students’ mathematics learning outcomes through learning interest. Penelitian ini tujuannya untuk mengetahui pengaruh fasilitas laboratorium komputer dan minat belajar terhadap hasil belajar mahasiswa. Merupakan penelitian kuantitatif jenis ex-post facto dengan variabel eksogen, endogen, dan variabel intervening. Populasi dan sampel penelitian ini ialah mahasiswa jurusan pendidikan matematika tahun ajar 2020/2021 berjumlah 80 orang. Instrumen yang digunakan yaitu angket dan tes tulis. Teknik analisis datanya yaitu analisis jalur. Berdasarkan penelitian yang telah dilakukan, diperoleh kesimpulan bahwa: (1) deskripsi fasilitas laboratorium komputer, minat belajar dan hasil belajar matematika mahasiswa secara berurut berada pada kategori sedang, tinggi, dan tinggi, (2) terdapat pengaruh langsung fasilitas laboratorium komputer terhadap hasil belajar matematika mahasiswa jurusan pendidikan matematika, (3) terdapat pengaruh langsung minat belajar terhadap hasil belajar matematika mahasiswa, (4) terdapat pengaruh langsung fasilitas laboratorium komputer minat belajar matematika mahasiswa jurusan pendidikan matematika, dan (5) terdapat pengaruh tidak langsung fasilitas laboratorium komputer terhadap hasil belajar matematika mahasiswa melalui minat belajar.